BANTUAN SOSIAL DAN EDUKASI MASYARAKAT TERDAMPAK KEBAKARAN RUMAH DI KAMPUNG BEALEBA DESA NENU KECAMATAN CIBAL KABUPATEN MANGGARAI - Adriani Tamo Ina Talu; Ingrida Umat; Imelda Siduk; Elfrida R Saputri; Didima Ria; Marselina Ebon; Bibiana Magisra (Unika Santu Paulus Ruteng, 2021)
The fire incident had an impact on the community in Bealeba Village, Nenu Village, Cibal District, Manggarai Regency. The fire incident occurred because of the negligence and carelessness of a family member who had a mental disorder. This situation makes family members and some of the residents' houses in the vicinity feel that they have lost both their houses and their assets. This issue is interesting to study and becomes the basis for conducting community service in the form of social assistance and education. This service activity aims to provide social assistance and education to people affected by fires so that the affected people are helped socially and economically and build their critical awareness about the dangers of fires in their homes / residences. Community service activities affected by the fire were carried out by adapting and modifying the IPOAI approach (identifying, planning, organizing, acting, impact).The results of the activity indicated that there was an increase in community awareness about the dangers of house / residence fires. The social assistance provided also helps people meet their daily needs.